MERAJUT KEBERSAMAAN : METAMORFOSIS TRADISI REWANG DI KELURAHAN BERENG BENGKEL KALIMANTAN TENGAH - Nada Ilmi; Dirja Indah; Muhammad Nor Said; Olivia (JUSAN: Jurnal Sejarah Peradaban Islam Indonesia, 2025)
Rewang tradition of the Javanese people, Rewang is a tradition in Javanese society where various human resources such as time, energy, and other gifts are used to help and ease the burden of whoever hosts the party. The purpose of this study is to find out the mechanism of acculturation of the Rewang tradition carried out by the Javanese community in Bereng Bengkel District, Central Kalimantan. The type of research uses a sociological approach based on socio-culture as the basic reference for the research. The theory used in this study is Durkheim's theory of mechanical solidarity. The method used also uses a qualitative method using the Miles and Huberman model data processing techniques by collecting relevant data and then after the data is collected in a reduction and the data is presented descriptively. The last step of the data presented in the interpretation is then drawn. This study uses primary data sources from the people of Bereng Bengkel Village who carry out the Rrewang tradition. Meanwhile, the secondary data source of this research is sourced from books, journal articles, or references similar to those studied. The results of this study show that the Rewang tradition is closely related to ethnicity, religion and culture. As is the case, Javanese Hinduism and kaharingan Hinduism which are the beliefs of the previous people. Javanese Hindus are closely related to the Javanese, while Kaharingan Hindus are also closely related to the Dayaks.